Subsisting in the mountains - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Subsistence Agriculture Improvement. Manual for the Humid Tropics Edited by F Goeltenboth, Brot für die Welt, Verlag Josef Margraf, Germany and the WAU Ecology Institute, Papua New Guinea. 1990. 230 pp. ISBN 9980 73 001 3 CTA number 973. 20 Credit po